Pengembangan Aplikasi Belajar Pegon Berbasis Android Dengan Menerapkan Metode User Centered Design - Evi Irhamillah Azza; Adam Hendra Brata; Arief Andy Soebroto (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Javanese-Arabic alphabet which is well-known as Pegon is an old code used as main alphabet for writing activities in Indonesia. Currently, the use of pegon is diminishing, it is used only by people in pesantren. In pesantren itself, Pegon is a subject taught in 45 minutes without the help of instructional media The learning of Pegon in a class is less effective although it is taught as a single subject. This case is caused by the lack of learning media in a learning process. In other case, if by chance the learning media is exist, it is limited and is not able to be used widely. By the condition found in the field of research, there is a need to develop an application of pegon with user-centered method. This application is designed to be user-experience oriented, so that it has enough usability value which is friendly to be used by teacher and student, and is able to make the learning of pegon more effective. Moreover, UCD method is iterative. It means UCD are able to dig every end-user need which is changeable directly. Result of this research is the availability of pegon learning application with usability examination using USE questionnaire. The application developed has feasibility average of usefulness criteria 89,14%, ease of use 100%, ease of learning 92,33%, satisfaction 92,33%, and usability using task scenario 95%.